2020
DOI: 10.1590/s1678-4634202046217120
|View full text |Cite
|
Sign up to set email alerts
|

Representações das emoções do trabalho docente em uma perspectiva histórica

Abstract: Resumo Este artigo apresenta os resultados de um estudo cujo objetivo foi identificar as representações, compreendidas na acepção de Chartier, a respeito das dimensões emocionais do trabalho dos professores primários em São Paulo, entre as décadas de 1950 e 1970. Utilizaram-se, para tanto, romances autobiográficos de professoras que exerceram o magistério no período, as revistas produzidas pelo Centro do Professorado Paulista - CPP, bem como as produções da Revista Brasileira de Estudos Pedagógicos – RBEP, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…The teachers who participated in this study, at the beginning of their work, showed fear and negative attitudes with remote work during the suspension of face-to-face classes due to Covid-19. This result allows us to infer that teaching in times of uncertainty and tension provokes in teachers the presence of certain negative emotions with greater or lesser intensity, amplitude, and continuity in pedagogical practice [25], [26].…”
Section: Discussionmentioning
confidence: 99%
“…The teachers who participated in this study, at the beginning of their work, showed fear and negative attitudes with remote work during the suspension of face-to-face classes due to Covid-19. This result allows us to infer that teaching in times of uncertainty and tension provokes in teachers the presence of certain negative emotions with greater or lesser intensity, amplitude, and continuity in pedagogical practice [25], [26].…”
Section: Discussionmentioning
confidence: 99%